TINJAUAN YURIDIS TERHADAP PEMOTONGAN TUNJANGAN JABATAN SECARA SEPIHAK OLEH PERUSAHAAN PT LUHAI INDUSTRIAL BERDASARKAN UNDANG-UNDANG NOMOR 6 TAHUN 2023 - Irwan Sapta Putra; Mohammad Hifni; Lucki Hidayanto (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2026)
This study aims to analyze the juridical review of unilateral position allowance deductions based on Law Number 6 of 2023, examine the legality of the position allowance deduction policy implemented by PT Luhai Industrial, and analyze the company's efforts to resolve the resulting disputes. This study employed an empirical juridical method with a qualitative approach. Data were collected through interviews with the Human Resources Development (HRD) department, production supervisors, and affected employees, supported by a literature review of primary, secondary, and tertiary legal materials. The data were analyzed using qualitative juridical analysis through data classification, analysis based on statutory regulations, and deductive conclusion drawing. The findings indicate that PT Luhai Industrial implemented position allowance deductions due to operational adjustments and cost-efficiency measures based on management decisions. However, the policy was implemented without employees' consent and without amendments to the employment agreements, rendering it inconsistent with the provisions of Law Number 6 of 2023 and resulting in suboptimal legal protection of employees' normative rights. Furthermore, the company's dispute resolution efforts remained limited to internal communication and did not prioritize participatory negotiation mechanisms. Therefore, greater transparency, employee involvement in decision-making affecting their economic rights, and the optimization of bipartite negotiations are necessary to strengthen the resolution of industrial relations disputes.